Patient engagement to examine perceptions of perinatal depression screening with the capabilities, opportunities, motivation, and behaviors (COM-B) model - Tabb, Karen M.; Hsieh, Wan-Jung; Sung, Jung Sun; Hoang, Tuyet Mai Ha; Deichen Hansen, Megan E.; Lux, Emily; Huang, Wen-Hao David (Frontiers in Health Services, 2022)
Background: Perinatal (during pregnancy and up until one year after birth) depression is one of the most common medical complications of pregnancy and is a major public health issue. The common early detection method to identify depression is to systematically administer depression screens to patients during their usual care clinic encounters. This study investigates how prenatal patients perceive depression screening and how screening informs their treatment to meet the specific needs of different racial and ethnic groups within both community and health care settings. Methods: Between June 2019 and August 2019, semi-structured in-depth interviews were conducted to explore participants’ experiences of depression screening with the Edinburgh Postnatal Depression Scale (EPDS). Perinatal women (N = 29) consented to participate in-depth, one-on-one qualitative interviews. Trained patient-researchers (n = 6), women who had previously experienced a perinatal mental health problem, were trained as research team members and facilitated the interviews alongside a research assistant. All interviews were recorded and transcribed verbatim. Data was analyzed with the use of Nvivo12. Thematic network analysis was used to analyze the data. Results: Through the in-depth patient engaged qualitative interviews this study uncovered several specific motivators and behaviors related to perinatal depression screening. Using directed content analysis, several themes within a COM-B frame emerged and could be reduced to themes and further divided into two different stages: the depression screening stage and the post-screening stage. Conclusions: The results of this qualitative study provide information for health care providers to improve, adjust, and assess the process of conducting perinatal depression screening among women. The data also provide information for health care facilities to identify a better screening tool and develop and measure their screening process. These findings are essential to design comprehensive patient-centered screening protocols given the increase in state and federal policies urging universal depression screening.